PEMBERDAYAAN MASYARAKAT DALAM MITIGASI, REKONSTRUKSI, DAN REHABILITASI PADA WILAYAH RAWAN BENCANA AKIBAT USAHA TAMBANG GALIAN GOLONGAN C DI KABUPATEN KAMPAR [COMMUNITY EMPOWERMENT IN MITIGATION, RECONSTRUCTION, AND REHABILITATION IN DISASTER-PRONE AREAS DUE TO CLASS C MINING WORKS IN KAMPAR DISTRICT] - Nurbit, Nurbit; Barlian, Eri; Heldi, Heldi; Rahmat, Hayatul Khairul (Perkumpulan Ahli Bimbingan dan Konseling Islam Indonesia, 2025)
This study aims to analyze community empowerment in mitigation, reconstruction, and rehabilitation in disaster-prone areas due to Class C mining operations in Kampar Regency. The primary focus of this research is to explore the role of community empowerment in addressing the environmental impacts caused by illegal mining, as well as the efforts that can be made to improve the social and economic conditions in these areas. The research method used is literature review, where the researcher analyzes various journals, books, articles, and previous studies that discuss topics related to community empowerment in the context of disasters and mining. The literature analyzed includes studies on the environmental impacts of Class C mining and the community empowerment strategies applied in disaster-prone areas. The results of the study show that low community participation in empowerment programs is a major barrier in mitigation and rehabilitation efforts. Communities around mining areas often lack awareness of the long-term environmental damage caused, and as a result, they are more focused on immediate economic benefits. Additionally, limited access to information, facilities, and budget constraints hinder the success of empowerment programs. This research recommends the development of an integrated database system, increasing community participation through education and training, and strengthening synergies between the government, communities, and the private sector in environmental rehabilitation efforts.